Exploring extreme environments in Türkiye for novel P450s through metagenomic analysis - Hande Mumcu; Julian Zaugg; Irem Keles; Aycan Kayrav; Nurgul Balci; David R. Nelson; Philip Hugenholtz; Elizabeth M. J. Gillam; Nevin Gul Karaguler (PLoS ONE, 2025)
Cytochrome P450 enzymes (P450s), particularly those of microbial origin, are highly versatile biocatalysts capable of catalyzing a broad range of regio- and stere-oselective reactions. P450s derived from extremophiles are of particular interest due to their potential tolerance to high temperature, salinity, and acidity. This study aimed to identify and classify novel microbial P450 enzymes from extreme environments across Türkiye, including hydrothermal springs, hypersaline lakes, and an acid-mine drainage site. The focus of this study was on classifying the sequence diversity of P450 enzymes in these sites. To that end, shotgun metagenomic analysis of six sites, using de novo binning, phylogenetic analysis, and functional gene annotation, was used to discover 311 putative P450 sequences, assigned to 87 families and 158 subfamilies, including 8 novel families and 49 new subfamilies. Of these, 237 were in 138 metagenomic bins, including 45 high-quality metagenome-assembled genomes. The distribution of P450 families varied across sites, reflecting distinct environmental conditions and microbial community compositions. These findings highlight the untapped potential of Türkiye’s extreme habitats as a source of novel biocatalysts. Beyond their industrial relevance, extremophile-derived P450s may also play key roles in enabling microbial adaptation to harsh environmental conditions, through their involvement in stress-responsive metabolic pathways and structurally resilient enzyme forms. This work provides a foundation for future studies into both their biotechnological applications and ecological functions.